Estimation of Nutrient Uptake Requirements for Yams in India Based on QUEFTS Model - K. R., Remya Remesh; G., Byju (JOURNAL OF ROOT CROPS, 2020)
Yams (Dioscorea Spp.) yield in many parts of the world are very low compared to maximum or potential yields. Managing the spatial and temporal variability using modeling approach will be one of the ways to improve the yield. The Quantitative Evaluation of Fertility of Tropical Soils (QUEFTS) model was used for determining the region specific balanced NPK uptake requirements and recommendations for a target yield of yams. Published data from several field experiments dealing with N, P and K during the past 30 years across yam growing environments with wide range of soil and climatic conditions were used for calibration of QUEFTS model. The calibration of QUEFTS model for yams required estimation of the slope of two borderlines describing the maximum accumulation (a) and maximum dilution (d) of N, P and K in plant in relation to tuber yield. The study proposed the following â€˜aâ€™ and â€˜dâ€™ values for yam with harvest index above 0.40. The constants for minimum (a) and maximum accumulation (d) (kg tuber kgâ€1 nutrient) of N (137 and 363), P (1212 and 3509) and K (127 and 397) were derived as standard model parameters. The ratio of maximum dilution (d) to maximum accumulation (a) [d/a] for N (2.65) was less than that of P (2.90) and K (2.91), indicating that a specific yield of yam relied on a relatively narrow range of N uptake. Therefore, a precise N supply is more important for a stable tuber yield relative to P and K. The model predicted a linear increase in tuber yield, if nutrients are taken up at rate of 4.15, 0.45 and 3.95 kg of N, P and K per 1000 kg tuber. The average uptake ratio in total plant dry matter was 9.2:1:8.8. The optimal internal efficiencies for balanced nutrition were 240, 2222 and 253 kg N, P and K per kg of tuber.